Comparative Study of Resistorless Filters Using Differential Voltage Current Controlled Current Feedback Operational Amplifiers and Differential Voltage Current Controlled Current Conveyors. (23rd September 2013) - Laoudias, Costas; Psychalinos, Costas
Abstract : Differential Voltage Current Controlled Current Feedback Operational Amplifier is an attractive active element for realizing resistorless filters with a minimum active component count. This is verified through a design example, where a 3rd-order leapfrog filter has been realized using the AMS 0.35  μ m CMOS process design kit. The performance of the Differential Voltage Current Controlled Current Feedback Operational Amplifier filter is evaluated and compared with that obtained by the corresponding filter, where Differential Voltage Current Controlled Current Conveyors have been employed.